Wellbeing of trans and gender‐diverse people with HIV in the United Kingdom: Results from Positive Voices 2022 - H. Kitt; C. Kelly; A. Aghaizu; M. Ross; F. C. Lampe; C. J. Smith; V. Martin; C. Humphreys; A. Brown; A. Sparrowhawk; M. Kall; J. Sewell; et al. (HIV Medicine, 2026)
Abstract Objectives This national cross‐sectional observational study aimed to assess mental health, quality of life, supportive network, experiences of HIV‐related stigma in healthcare and unmet service need among trans and gender‐diverse people with HIV, compared to cisgender people with HIV. Methods Positive Voices 2022 is a questionnaire survey of people accessing HIV care in England, Scotland and Wales carried out in 2022 and 2023 that included measures of depression and anxiety symptoms and suicidal ideation (PHQ‐9 and GAD‐7), health‐related quality of life (EQ‐5D‐5L), supportive network (modified Duke FSSQ), experiences of HIV‐related stigma in healthcare and service needs. Logistic and ordinal logistic regression assessed the association of gender identity with these measures unadjusted and adjusted for age group and ethnicity. Results Overall, 67 trans or gender‐diverse and 4551 cisgender people with HIV participated. Compared to cisgender participants, trans and gender‐diverse participants were younger, more likely to be Asian and less likely to be black. They were less likely to be in employment, homeowners and financially secure. Trans and gender‐diverse participants had a higher prevalence of depression symptoms (35.5% [22/62] vs. 20.5% [865/4219], adjusted odds ratio [aOR] [95% confidence interval, CI] = 1.96 [1.15, 3.34]; p = 0.014) and suicidal ideation (37.1% [23/62] vs. 14.6% [616/4219]; aOR = 3.09 [1.85, 5.17]; p < 0.001) compared to cisgender participants. They also had poorer health‐related quality of life for three domains (anxiety and depression, usual activities and self‐care) and lower levels of supportive network in unadjusted and adjusted analyses. A higher proportion of trans and gender‐diverse participants than cisgender participants had unmet needs for health services, including mental health services (49.2% [31/63] vs. 30.2% [1310/4343]; aOR = 2.02 [1.22–3.35]; p = 0.007), lifestyle services, and welfare and social services. Conclusions Trans and gender‐diverse people with HIV have poorer mental health and wellbeing than cisgender people with HIV, and a higher prevalence of unmet service needs, highlighting the need for access to culturally competent mental health and other health and welfare services.